2015
DOI: 10.1161/circulationaha.115.016795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Atrial Myopathy Underlying Atrial Fibrillation

Abstract: Atrial disease or myopathy forms the substrate for atrial fibrillation (AF) and underlies the potential for atrial thrombus formation and subsequent stroke. Current diagnostic approaches in patients with AF focus on identifying clinical predictors with evaluation of left atrial size by echocardiography serving as the sole measure specifically evaluating the atrium. Although the atrial substrate underlying AF is likely developing for years prior to the onset of AF, there is no current evaluation to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(36 citation statements)
references
References 194 publications
(164 reference statements)
1
34
0
1
Order By: Relevance
“…9 Proposed underlying mechanisms could relate to a reduced cardiac output, cardiac remodeling, or underdeveloped cerebral collateral circulation. 9,24,25 Although our results are in line with prior observations that AF carries an excess risk for poor outcome independent of underlying heart disease; 26 our study design did not enable us to conduct detailed electro- and echocardiographic investigations to clarify this issue. Further, studies on the robustness of cerebral collateral circulation among patients with large artery infarction did not demonstrate a significant difference between patients with vs. without AF.…”
Section: Discussionsupporting
confidence: 72%
“…9 Proposed underlying mechanisms could relate to a reduced cardiac output, cardiac remodeling, or underdeveloped cerebral collateral circulation. 9,24,25 Although our results are in line with prior observations that AF carries an excess risk for poor outcome independent of underlying heart disease; 26 our study design did not enable us to conduct detailed electro- and echocardiographic investigations to clarify this issue. Further, studies on the robustness of cerebral collateral circulation among patients with large artery infarction did not demonstrate a significant difference between patients with vs. without AF.…”
Section: Discussionsupporting
confidence: 72%
“…This likely reflects the underlying atrial myopathy responsible for the AF. 29 While the LAA is the most common site for thrombus formation in AF, the underlying pathophysiology for this has not been elucidated. Moreover, only a minority of patients with AF, even without anticoagulation, develop LA thrombi, suggesting that there are patient-specific factors that promote thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between AF and stroke has been established in multiple epidemiological studies, the exact mechanism of stroke remains poorly understood [11]. Multiple studies have shown a correlation between thromboembolic risk and asymptomatic AF episodes of variable duration detected through implantable devices [26-29], even though a temporal association of an incident stroke with an antecedent AF episode was frequently absent in the aforementioned studies [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus formation in the left atrium is thought to represent the main source of thromboembolic events in patients with AF [11]. Consistent with recent evidence suggesting that paroxysmal AF may be associated with a lower incidence of stroke compared to persistent AF [12-15], we hypothesized that in a selected group of patients with paroxysmal AF and a low risk of stroke, maintaining therapeutic anticoagulation only during episodes of AF (either symptomatic or asymptomatic) may provide the benefits of continuous anticoagulation in terms of stroke prevention, while decreasing the risk of bleeding complications.…”
Section: Introductionmentioning
confidence: 99%